Absence of Rgs5 Influences the Spatial and Temporal Fluctuation of Cardiac Repolarization in Mice - Song, Zi-liang; Liu, Yang; Liu, Xu; Qin, Mu (Frontiers in Physiology, 2021)
Aims: This study investigated the contribution of the regulator of G-protein signalling 5 (Rgs5) knockout to alteration of action potential duration (APD) restitution and repolarizing dispersion in ventricle. Methods and Results: The effects of Rgs5-/- were investigated by QT variance (QTv) and heart rate variability analysis of Rgs5-/- mice. Monophasic action potential analysis was investigated in isolated Rgs5-/- heart. Rgs5-/- did not promote ventricular remodelling. The 24-hour QTv and QT variability index (QTVI) of the Rgs5-/- mice were higher than those of wild-type (WT) mice (P <0.01). In WT mice, a positive correlation was found between QTv and the standard deviation of all NN intervals (r = 0.62; P <0.01), but not in Rgs5-/- mice (R = 0.01; P> 0.05). The absence of Rgs5 resulted in a significant prolongation of effective refractory period and APD in isolated ventricle. In addition, compared with WT mice, the knockout of Rgs5 significantly deepened the slope of the APD recovery curve at all 10 sites of the heart (P<0.01), and increased spatial dispersions of Smax (COV-Smax) (WT ：0.28±0.03, Rgs5-/-:0.53±0.08, P<0.01). Compared with WT heart, Rgs5-/- increased the induced S1–S2 interval at all sites of heart and widened the window of vulnerability of ventricular tachyarrhythmia (P < 0.05). Conclusion：Our findings indicate that Rgs5-/- is an important regulator of ventricular tachyarrhythmia in mice by prolonging ventricular repolarization and increasing spatial dispersion in ventricle.